(untitled) (مجلة العلوم الشاملة, 2025)
The present study focused on the feasibility of Organic Rankine Cycle (ORC) using waste heat recovery. The waste heat covered from glass factory. The working fluid in the cycle were Isobutane. Thermodynamic model of the system was derived and validated for performance prediction. The validated thermodynamic model is used to optimize the operation of the small ORC in waste heat recovery application. The temperature which recovered and mass flow rate were 155 ºC and 27 kg/s respectively. The power output of double stage turbines was 8370 kW .The payback period 2.5 years. It is concluded from the study that recovering the waste heat by way of ORCs is technically and economically feasible. As recycled energy, waste heat has the same advantages as renewable energy.